A reconfigurable CBP/LP active RC filter with noise-shaping technique for wireless receivers - 刘琼冰 俞小宝 张俊峰 续阳 池保勇 (Journal of semiconductors, 2014)
A reconfigurable complex band-pass （CBP）/low-pass （LP） active-RC filter with a noise-shaping technique for wireless receivers is presented. Its bandwidth is reconfigurable among 500 kHz, 1 MHz and 4 MHz in LP mode and 1 MHz, 2 MHz and 8 MHz in CBP mode with 3 MHz center frequency. The Op-Amps used in the filter are realized in cell arrays in order to obtain scalable power consumption among the different operation modes. Furthermore, the filter can be configured into the 1st order, 2nd order or 3rd order mode, thus achieving a flexible filtering property. The noise-shaping technique is introduced to suppress the flicker noise contribution. The filter has been implemented in 180 nm CMOS and consumes less than 3 mA in the 3rd 8 MHz-bandwidth CBP mode. The spot noise at 100 Hz can be reduced by 14.4 dB at most with the introduced noise-shaping technique.